Self‐Assembled Room Temperature Multiferroic BiFeO3‐LiFe5O8 Nanocomposites. (24th October 2019) - Sharma, Yogesh; Agarwal, Radhe; Collins, Liam; Zheng, Qiang; Ievlev, Anton V.; Hermann, Raphael P.; Cooper, Valentino R.; KC, Santosh; Ivanov, Ilia N.; Katiyar, Ram S.; Kalinin, Sergei V.; Lee, Ho Nyung; et al.
Abstract: Multiferroic materials have driven significant research interest due to their promising technological potential. Developing new room‐temperature multiferroics and understanding their fundamental properties are important to reveal unanticipated physical phenomena and potential applications. Here, a new room temperature multiferroic nanocomposite comprised of an ordered ferrimagnetic spinel α‐LiFe5 O8 (LFO) and a ferroelectric perovskite BiFeO3 (BFO) is presented. It is observed that lithium (Li)‐doping in BFO favors the formation of LFO spinel as a secondary phase during the synthesis of Li x Bi1− x FeO3 ceramics. Multimodal functional and chemical imaging methods are used to map the relationship between doping‐induced phase separation and local ferroic properties in both the BFO‐LFO composite ceramics and self‐assembled nanocomposite thin films. The energetics of phase separation in Li doped BFO and the formation of BFO‐LFO composites are supported by first principles calculations. These findings shed light on Li's role in the formation of a functionally important room temperature multiferroic and open a new approach in the synthesis of light element doped nanocomposites for future energy, sensing, and memory applications. Abstract : An approach to create a robust room temperature multiferroic using light element doping is demonstrated. The synthesis of self‐assembled ferrimagnetic LiFe5 O8 nanopillars heteroepitaxially embedded in a single crystal ferroelectric BiFeO3 matrix provides new avenues for designing multifunctional energy, sensing, and computing applications.